2019
DOI: 10.1089/neu.2017.5608
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Depression after Traumatic Brain Injury in a Large National Sample

Abstract: Depression is associated with poorer recover after traumatic brain injury (TBI), yet awareness of depression risk post-TBI among providers and patients is low. The aim of this study was to estimate risk of depression post-TBI among adults 18 years of age and older and to identify risk factors associated with developing depression post-TBI. We conducted a retrospective, matched cohort study using claims data for privately insured and Medicare Advantage enrollees in a large U.S. health plan. Adults ≥18 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 35 publications
4
40
2
1
Order By: Relevance
“…The true prevalence of depression in the chronic period following mTBI is uncertain, with most studies focusing on mTBI in the acute phase (days-weeks) as part of a constellation of post-concussive symptoms or on moderate-to-severe injuries. Suggested risk factors for post-TBI depression are heterogeneous across available data; indeed, no clear consensus has emerged regarding such factors such as female sex (11)(12)(13) and age at injury (14,15). Moreover, the likelihood of depression following mTBI sustained via different injury modalities has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The true prevalence of depression in the chronic period following mTBI is uncertain, with most studies focusing on mTBI in the acute phase (days-weeks) as part of a constellation of post-concussive symptoms or on moderate-to-severe injuries. Suggested risk factors for post-TBI depression are heterogeneous across available data; indeed, no clear consensus has emerged regarding such factors such as female sex (11)(12)(13) and age at injury (14,15). Moreover, the likelihood of depression following mTBI sustained via different injury modalities has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…About 50-60% of patients with severe TBI often exhibit these disturbances and have difficulties impacting multiple domains of functioning such as occupation, interpersonal relationships, and sexual functioning. Depression and anxiety are the most commonly reported emotional disturbances after TBI and can negatively affect the long term outcomes (Albrecht, Barbour, Abariga, Rao, & Perfetto, 2019;Scholten et al, 2016;War, Jamuna, & Arivazhagan, 2014). The loss of employment secondary to TBI can have further cascading effects on finances, interpersonal relationships, and quality of life (Ahmed et al, 2017;Benedictus, Spikman, & van der Naalt, 2010).…”
Section: Posttraumatic Sequelaementioning
confidence: 99%
“…A number of studies have established that TBI increases the risk of mood disorders, personality changes and substance use disorders. [13][14][15] A study by Tateno et al revealed that the prevalence of pathological laughing and crying (PLC) during the first year after TBI was 10.9%, and that compared with patients without PLC, patients with PLC had significantly more depressive, anxious and aggressive behaviours and had poorer social functioning. 16 This conclusion is consistent with a recently published article that considers neurological aspects of Joker's disease and assumes that he suffers from neuropsychiatric sequelae related to childhood TBI involving the frontotemporal regions and, in particular, the lateral aspect of the left frontal lobe.…”
Section: Pseudobulbar Affectmentioning
confidence: 99%